Expressão do sexo, crescimento e produção de pepino (Cucumis sativus L.) com emprego de substâncias reguladoras de crescimento - Machado dos Santos, Alverides; Fernandes Lopes, Nei (Revista Ceres, 2025)
Sex expression, growth and yield, as affected by growth regulators, were studied in three cultivars (Verde Pequeno de Paris, Boston Pickling and Wisconsin SMR-18) of cucumber (Cucumis sativus L.). Gibberellic acid (GAg) (0, 100 and 200 ppm), naphathalenoacetic acid (NAA) (0,100 and 200 ppm), (2 — chloroethyl)-trimethylammonium chloride (CCC) (0, 250 and 500 ppm) and 2,3, 5-trilodobenzoic acid (TIBA) (0, 25 and 50 ppm) were used as water sprays on the young plants in the 3-4 true leaf stage. The experiment was carried out in the field, using a splitsplit plot randomized block design with three replications.